2018
DOI: 10.2174/1570162x16666180910130112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Transmitted HIV-1 Drug Resistance Mutations Using Ultra- Deep Pyrosequencing in a Turkish Cohort

Abstract: UDPS was used for the first time to assess TDRM in a Turkish HIV cohort and uncovered several mutations hidden within minority variants. UDPS may be preferred to detect PDRMs for avoiding virologic failure with rilpivirine-based ART regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Additional articles were identified by experts in the field. We screened out 1330 studies after removing duplicates, and 140 articles were downloaded for full-length screening, of which 39 articles were kept [ 6 , 17 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional articles were identified by experts in the field. We screened out 1330 studies after removing duplicates, and 140 articles were downloaded for full-length screening, of which 39 articles were kept [ 6 , 17 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…NGS technologies to test for HIV drug resistance in Turkey is a newly developing area with a very limited amount of data. Sili et al 34 used NGS to study the PR and RT gene regions in 36 HIV‐1‐positive plasma samples, and identified 8.3% ( n = 3) mutations at a frequency of above 20% and 30.6% ( n = 11) mutations at a frequency above 2%. Good technical experience and strong bioinformatics knowledge are critical if NGS technologies are to be used to test ARV drug resistance in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that result in resistance to ETR and RPV have been observed in HIV isolates from both adults [40,74,117,120,124,125] as well as children and adolescents [64,126], where higher non-adherence may lead to a higher frequency of virologic failure. Drug-resistant strains that have been seen in children have often shown partial susceptibility to ETR and RPV [126].…”
Section: Resistance To Dapysmentioning
confidence: 99%
“…Combinations of NNRTI-resistance mutations have been common among RPV patients in virologic failure[117,126]. HIV-1 RT mutations in the NNRTI-binding site that result in resistance against ETR and/or RPV in certain combinations have included V90I, A98G, L100I/V, K101E/P/Q/R/T, K103N/S, V106A/I, V108I, E138A/G/K/Q/R/S, V179F/I/L/D, Y181C/I/V, Y188H/L, G190A/C/E/Q/S/T/V, H221Y, P225H, F227C/L, and M230I/L (Figure 2)[40,59,61,64,74,117,118,120,121,[124][125][126][127][129][130][131][132][133]. V179F + Y181C + F227C is an example of a combination of mutations that confers high resistance to both ETR and RPV(Table 2)[59].…”
mentioning
confidence: 99%